Information women receive after recurring pregnancy loss in the antenatal setting of an academic hospital in Tshwane, South Africa - Yazbek, Mariatha (University of Pretoria, 2023)
Dissertation (MSc (Advanced Midwifery and Neonatal Science))--University of Pretoria, 2022.